Background ground neuro-histopathological lesions in Indian buffaloes (Bubalus bubalis) - KUMAR, R; SINGH, R; SINGH, K P; DWIVEDI, P; CHAUHAN, R S (The Indian Journal of Animal Sciences, 2011)
Brains of 321 buffaloes, aged 5-7 years and of either sex, were collected randolnly during routine slaughter for generating baseline data on neurohistopathologicallesions. Brains (124/321 (38.62%)) showed lnicroscopic lesions: chromatolysis of neurons in 5 (1.56%), ischen1ic neurons in 29 (9.03%), Lafont bodies in 1 (0.31 %), neurolnelanins in 45 (14.01 %), engorgement of vasculature in 17 (5.300/0), haeITIOIThages in 25 (7.790/0), vasogenic oedema ofaxonic tracts in 2 (0.62%), proteinaceous globules in vascular lumen in 3 (0.93%), vacuolation of white matter in 11 (3.420/0), neuropil vacuolation in 2 (0.62%), perivascular cuffing in 46 (14.33%), vasculitis in 5 (1.560/0 ),microgliosis in 58 (18.06%), nonsuppurative meningoencephalitis in 5 (1.56%), neuronophagic nodule in 1 (0.31 %), satellitosis in 5 (1.56%), astrogliosis in 4 (1.250/0), oligodendrogliosis in 3 (0.93%), subependymal gliosis in 2 (0.62%), parasitic infestation in 1 (0.31 %), and pineal gland calcification in 22/54 (40%) cases. The lesions were present either singly or in combination, being maxin1um in rostral colliculi followed by cerebnlm and the caudate nucleus, while other sites also showed similar combination of lesions. Though several kinds of lesions were recorded, yet a case of Lafora bodies seems to be the first report in this species. Neuromelanins and perivascular cuffing were the 1110St frequently occun'jng lesions. The lesions were incidental in nature as there was no history of nervous symptoms in these cases. BSEwas not detected in any buffalo.Â